2010
DOI: 10.1097/rhu.0b013e3181d59d46
|View full text |Cite
|
Sign up to set email alerts
|

What Was the Patient's Occupation?

Abstract: T he computed tomography (CT) scan shows characteristic but uncommon lesions, which are the results of almost 50 years of exposure.A 55-year-old woman was suffering from pains in the feet. X-rays and the CT scan (sagittal CT scan reconstruction of the left foot to show areas of the lesions) showed a bilateral flatfoot and a localized degenerative lesion of the tarsometatarsal joint. The joint between the medial cuneiform and the first metatarsal bone was particularly affected, so was the joint between the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Bernard and colleagues [24] reported that stair climbing was associated with foot OA. Descatha and Deschamps [51] reported the case of a 55-year old woman suffering from pains in the feet. Over 40 years as a professional dancer and dance teacher caused localized OA of the tarsometatarsal joint, or at least accelerated the degenerative process.…”
Section: Occupational Risk Factors For Osteoarthritismentioning
confidence: 99%
“…Bernard and colleagues [24] reported that stair climbing was associated with foot OA. Descatha and Deschamps [51] reported the case of a 55-year old woman suffering from pains in the feet. Over 40 years as a professional dancer and dance teacher caused localized OA of the tarsometatarsal joint, or at least accelerated the degenerative process.…”
Section: Occupational Risk Factors For Osteoarthritismentioning
confidence: 99%
“…lower educational attainment, and (a history of) physically demanding occupation (e.g. frequent stair climbing, professional dance) appear to contribute more to the risk of MTP1 clinical or radiographic OA in the general population, and primary OA [52,74,73,75], and we therefore assume that the combination of biomechanical factors, including acromegaly-related physical changes (e.g. feet enlargement, joint misalignment), contribute most to the development of MTP1 OA in acromegaly.…”
Section: Discussionmentioning
confidence: 99%
“…lower educational attainment, and (a history of) physically demanding occupation (e.g. frequent stair climbing, professional dance) appear to contribute more to the risk of MTP1 clinical or radiographic OA in the general population, and primary OA [ 54 , 75 77 ], and we therefore assume that the combination of biomechanical factors, including acromegaly-related physical changes (e.g. feet enlargement, joint misalignment), contribute most to the development of MTP1 OA in acromegaly.…”
Section: Discussionmentioning
confidence: 99%